Spatiotemporal Pattern of Vulnerability to Climate Change in Madhya Pradesh, India - George, Alinda; Sharma, Pritee; Pradhan, Kalandi Charan (Applied spatial analysis and policy, 2024)
Climate change and its associated impacts are more severely felt in Madhya Pradesh than in other Indian states, mainly because of acute poverty and social vulnerability in the state. This paper attempts to assess inter-spatial and inter-temporal vulnerability to climate change using a Climate Vulnerability Index, an aggregate of the Climate Index and the Composite Social Vulnerability Index. The Climate Index represents the exposure to climate change, and the social vulnerability represented by the Composite Social Vulnerability Index consists of two subindices: Socioeconomic Vulnerability Index and Infrastructural Vulnerability Index. The indices are computed using Principal Component Analysis for three rounds of census data (1991, 2001, and 2011). The study found a significant decrease in composite social vulnerability and subindices over the decades. At the same time, the Climate Index shows a significant increase over the decades, leading to a nonsignificant increase in climate vulnerability in the recent decade. The study advocates for targeted interventions to reduce social vulnerability further to cope with the increasing exposure to climate change; hence, overall vulnerability can be reduced. Targeted interventions for livelihood diversification, education, inclusive growth, and infrastructural facilities in tribal-dominated districts will be crucial, given the likelihood of climatic variation in the future.